Iran Nuclear Deal: Assessing its Future Trajectory - Ms. Sitara Noor (CISS Insight Journal, 2016)
The Joint Comprehensive Plan of Action (JCPOA) was concluded between Iran and E3/EU+3 (US, UK, France, China, Russia and Germany with the High Representative of the European Union for Foreign Affairs and Security Policy) on14 July 2015. It has successfully completed its first year, notwithstanding concerns and surrounding tensions. So far, the deal is on track to meet the deadlines set for its implementation over the next ten years. The conclusion of the JCPOA is a significant event in the history of nuclear diplomacy in a number of ways. It not only broke the impasse on the decade long Iranian nuclear issue which had gripped the world with the fear of another war in the region, but also changed the security landscape of the Middle East. Being among the first few countries to sign and ratify the Nuclear Nonproliferation Treaty (NPT), Iran had already embarked on an ambitious civil nuclear programme under the Shah’s regime. Its nuclear programme, however, came under fire when Iran was found to be involved in some suspicious activity involving undeclared nuclear material and facilities. What followed was a tumultuous period leading to a deadly stalemate with impending danger of another regional crisis.